The Analysis of Community Availability for Covid-19 Vaccine in Banda Aceh City - Mhd. Hidayattullah; Nurjannah Nurjannah; Irwan Saputra (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
Vaccines are considered as an effort to reduce the spread of COVID-19, but in some circles there are still doubts about the effectiveness of the vaccine. In Indonesia, Aceh and West Sumatra are the 2 provinces with the lowest vaccine receipts with acceptance rates still below 50%. Objective: To determine the relationship of factors (perceived susceptibility, perceived severity, perceived benefits, perceived barriers, and cues to action) on the availability of the COVID-19 vaccine. Research Methods: Using a cross-sectional method with a research sample of 439 respondents. Statistical analysis used in the form of chi square test and logistic regression test using a computer program. Research Results: From the results of the chi square test, it was found that there was a relationship between susceptibility, severity, benefits, barriers, and cues to the readiness of the COVID-19 vaccine with (p≤0.05). Conclusion: The most dominant factor related to the public's willingness to the COVID-19 vaccine in this study was the perceived benefit.